Religious Moderation in Habib Ja'far Husein's Da'wah on Tiktok Media - Novarita, Cindy; Kusuma, Wira Hadi; Ramdhani, Rahmat (UIN Fatmawati Sukarno Bengkulu, 2024)
Da'wah is one of the right approach solutions in every aspect of life by preachers such as Habib Jafar Husein through the TIktok digital platform. The phenomenon of using social media as a means of da'wah is increasingly growing, including on Tiktok which is a short video platform that is currently popular. This research aims to analyze how Habib Jafar Husein uses Tiktok as a tool to spread messages of religious moderation to Tiktok users. The research method used is a case study with a qualitative approach. The research results show that Habib Jafar Husein uses TikTok effectively to convey messages of religious moderation to his audience. Through short videos that are intelligent, inspiring and entertaining, Habib Jafar Husein is able to attract the attention of TikTok users and convey religious values in an interesting and easy to understand way. This research contributes to the understanding of the use of social media in da'wah activities, in particular in the context of TikTok. Apart from that, this research also provides an insight into how a ulama can adapt to technological developments to reach a wider audience in spreading religious messages.